Histone recognition and large-scale structural analysis of the human bromodomain family. - Filippakopoulos, P; Picaud, S; Mangos, M; Keates, T; Lambert, J; Barsyte-Lovejoy, D; Felletar, I; Volkmer, R; Müller, S; Pawson, T; Gingras, A; Arrowsmith, C; et al. (2012)
Bromodomains (BRDs) are protein interaction modules that specifically recognize ε-N-lysine acetylation motifs, a key event in the reading process of epigenetic marks. The 61 BRDs in the human genome cluster into eight families based on structure/sequence similarity. Here, we present 29 high-resolution crystal structures, covering all BRD families. Comprehensive crossfamily structural analysis identifies conserved and family-specific structural features that are necessary for specific acetylation-dependent substrate recognition. Screening of more than 30 representative BRDs against systematic histone-peptide arrays identifies new BRD substrates and reveals a strong influence of flanking posttranslational modifications, such as acetylation and phosphorylation, suggesting that BRDs recognize combinations of marks rather than singly acetylated sequences. We further uncovered a structural mechanism for the simultaneous binding and recognition of diverse diacetyl-containing peptides by BRD4. These data provide a foundation for structure-based drug design of specific inhibitors for this emerging target family.